Paradoks Pembaruan Hukum Pidana terhadap Pengurangan Ancaman Pidana Minimum Tindak Pidana Korupsi dalam Kitab Undang-Undang Hukum Pidana - Aswindari Harahap; Ismaidar Ismaidar; Abdul Rahman Maulana Siregar; Alfonso Pahala Manihuruk; Bambang Agus Pariyono; Briski Viktor Sinaga; Derta Simbolon (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Corruption has long been regarded as an extraordinary crime due to its extensive impact on state finances, the national economy, and public trust in government institutions. As part of Indonesia’s commitment to combating corruption, Law Number 31 of 1999 concerning the Eradication of Corruption Crimes established relatively severe special minimum penalties, particularly under Article 2 paragraph (1). However, through Law Number 1 of 2023 concerning the Criminal Code, corruption offenses were reformulated under Articles 603 to 606, including changes to the minimum criminal sanctions for certain corruption offenses. This study aims to analyze the reformulation of corruption offenses in the Criminal Code and to examine the paradox arising from the reduction of minimum criminal penalties within Indonesia’s criminal law reform policy. This research employs a normative legal research method using statutory and conceptual approaches. The data utilized are secondary legal materials collected through library research and analyzed qualitatively. The findings reveal that Article 603 of the Criminal Code substantially adopts the provisions of Article 2 paragraph (1) of Law Number 31 of 1999, while reducing the minimum imprisonment from four years to two years. This change reflects a new orientation emphasizing sentencing flexibility and individualization of punishment. Nevertheless, it also creates a paradox because the reduction applies to corruption, an offense that has long been classified as an extraordinary crime. Therefore, Indonesia’s criminal law reform continues to face challenges in balancing the modernization of the sentencing system with the consistency of anti-corruption policies.